Research on the impact of China's high-speed rail opening on enterprise market power: Based on the perspective of market segmentation. (November 2022) - Xu, Fei; Liu, Qian; Zheng, Xingdong; Cao, Luqi; Yang, Mian
Abstract: China's regional market segmentation weakens the market mechanism, creates convenience for enterprises with high market share to obtain market power, and will eventually reduce the effectiveness of market competition. However, infrastructure such as high-speed rail (HSR) can break the market segmentation and improve the effectiveness of market competition. In this end, based on the data of Chinese A-share listed companies from 2007 to 2019, this paper constructed a quasi-natural experiment model to examine the relationship between the opening of high-speed railway and the effectiveness of market competition. This paper finds that: (1) the opening of HSR can help restrain the market power of enterprises with high market share; (2) the opening of HSR has a more significant effect on spatially dispersed industries, low capital-intensive enterprises, non-eastern enterprises, manufacturing industries and non-heavy asset industries; (3) the opening of HSR will inhibit the advantages of enterprises with high market share in expanding sales and R&D innovation, thus reducing their market power. The conclusion still holds after considering important factors such as city administrative level, traditional transportation capacity, company stock price crash risk and merger and reorganization (M&A). The findings of this paper mean that the space-time compression effect brought by the opening of HSR will reduce the market power of enterprises brought by market segmentation, and then improve the effectiveness of market competition. Therefore, we should fully tap the value of HSR to help high-quality economic development. Highlights: A theoretical framework of " HSR Opening, Market Segmentation, and Enterprise Market Power " is built. Market segmentation weakens advantages of cross-regional operations and distort market competition. The infrastructure such as HSR can break the market segmentation and improve the effectiveness of market competition. Opening of HSR can help restrain the market power of enterprises with high market share. Opening of HSR will inhibit the advantages of enterprises with high market share in expanding sales and R&D innovation, thus reducing their market power.